Profil Hematologi dan Urinalisis pada Kambing Kacang yang Terinfeksi Sarcoptes scabiei - Deran Ola, Elisa Albertine Rahmita; Wuhan, Yustinus Oswin Primajuni (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2024)
Capra aegagrus hircus are local goats native to Indonesia with great potential to be developed to meet animal protein needs. The success of Capra aegagrus hircus rearing is closely related to husbandry management. Health management is an important factor in the livestock industry as it has a direct impact on productivity, animal welfare, and public health. To maintain animal health, it is necessary to conduct routine clinical examinations such as hematology and urinalysis. In this case, a Capra aegagrus hircus less than 1 year old, belonging to Undana's dry land, had been sick for 3 weeks. The clinical symptoms that appeared referred to the incidence of scabiosis. The examinations performed were skin scraping, hematological examination, and urinalysis. The results of the Capra aegagrus hircus examination were positive for Sarcoptes scabiei infection with hypochromic normocytic anemia and urinalysis results found struvite crystal sedimentation and suspected methemoglobin compounds in the urine